Pengembangan Dashboard Penjualan Tiket di Kaldera Toba Nomadic Escape - Sianturi, Riyanthi Angrainy; Simamora, Daniel Alex Candra (Universitas Nusa Cendana, 2024)
Lake Toba has been designated as one of Indonesia's Super Priority Tourism Destinations (DPSP). The Kaldera Toba Nomadic Escape is a tourist attraction within the Lake Toba DPSP area, managed by the Lake Toba Authority (BPODT). Visitors to the Toba Caldera tourist area often face challenges, particularly those from outside the region who cannot book tickets online. Additionally, ticket sales data at Caldera is still managed manually using traditional bookkeeping methods, which prevents immediate compilation and accurate reporting of sold tickets. There are two categories of ticket bookings available at the Toba Caldera: entry tickets for general tourist access and event tickets, which are only available when events are organized at the Kaldera Toba Nomadic Escape. To facilitate easier management of ticket bookings at the Kaldera Toba Nomadic Escape, a web-based system has been developed, enabling visitors to book tickets online. This system includes a dashboard that allows for real-time transaction recapitulation. The system development follows the Waterfall model, which consists of several stages: Communication, Planning, Modeling, Construction, and Deployment. In developing the ticket sales dashboard, a comparative analysis of several previous studies was also conducted to enhance the visual details and functionality of the ticket sales dashboard. As a result of this research, a web-based ticket booking system and sales dashboard were developed. The ticket booking system allows visitors to easily purchase tickets, while the sales dashboard enables the Kaldera Toba Nomadic Escape management to monitor important statistics, such as the number of visitors, ticket sales, and the availability of tickets in real-time.